Tax culture in MSEs and tax collection - Chirinos De La Cruz , Liliana Milagros; Gálvez Ñañez, Federico Ricardo; Dionicio Barazorda, Lourdes Isabel (mktDESCUBRE; Vol 1 No 21 (2023): Twenty-first Edition (January - June), 2023)
The objective of the article is to determine the relationship that exists between the tax culture in MYPES and tax collection. The purpose is to demonstrate that, the more tax culture or ignorance of tax regulations in taxpayers, the less will be the non-compliance with their obligations. taxes, therefore, affects tax collection. Original research article; resulting from a mixed approach investigation of descriptive, longitudinal level and non-experimental design. The population of taxpayers of micro and small companies in the department of Lima. The documentary, statistical analysis technique was applied using the database of public institutions linked to tax reports and reports. The results show that tax collection in the MYPES sector has been reduced in this way, in the MYPES tax regime in the single simplified regime due to the lack of tax culture and the informality of the merchants. It is concluded that there is a significant relationship between the tax culture of MYPES and tax collection, which indicates opting for tax culture mechanisms with specific awareness strategies, knowledge of formalization acts and their advantages.